Universal Detection of Mia Antigen and Frequencies of Glycophorin Hybrids among Blood Donors in Taiwan by Human Monoclonal Antibodies against Mia (MNS7), Mur (MNS10), and MUT (MNS35) Antigens - Meng-Hua Yang; Jen-Wei Chen; Kaito Sayaka; Makoto Uchikawa; Nelson H. Tsuno; Sheng-Tang Wei; Sheng-Mou Hou; Yann-Jang Chen (Diagnostics, 2021)
Glycophorin hybrids such as GP.Mur are common in Southeast Asians. In Taiwan, clinically significant alloantibodies to the GP.Mur phenotype are the most important issue in blood banks. A large-scale screening of glycophorin hybrids in the Taiwanese population is urgently needed to ensure transfusion safety. Four clones of human hybridomas that secrete anti-Mia, anti-MUT, and anti-Mur were established by fusing human B-lymphocytes and myeloma cells (JMS-3). The specificity of each monoclonal antibody (MoAb) was characterized. Three MoAbs were applied on an Automated Pretransfusion Blood Testing Analyzer (PK7300/PK7400) for donor screening. Genotyping was performed to determine the detailed subgrouping of glycophorin hybrids. Four MoAbs are IgM antibodies. Anti-Mia (377T) binds to 46DXHKRDTYA54, 48HKRDTYAAHT57 peptides, and anti-Mia (367T) binds to 43QTNDXHKRD51 peptides (X indicates T, M, or K). Anti-Mur is reactive with 49KRDTYPAHTA58 peptides. Anti-MUT is reactive with 47KHKRDTYA54. A total of 78,327 donors were screened using three MoAbs, and 3690 (4.71%) were GP.Mur, 20 (0.025%) were GP.Hut, and 18 (0.022%) were GP.Vw. When the Mia antigen was introduced as routine screening, the frequency of Mi(a+) among blood donors in Taiwan was 4.66% (67,348/1,444,541). Mia antigen was implemented as a routine blood testing, and the results were labeled on all red blood cell (RBC) units.